2019
DOI: 10.1371/journal.pone.0210681
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-locus characterization and phylogenetic inference of Leishmania spp. in snakes from Northwest China

Abstract: Background Leishmaniasis caused by protozoan parasite Leishmania is a neglected disease which is endemic in the northwest of China. Reptiles were considered to be the potential reservoir hosts for mammalian Leishmaniasis, and Leishmania had been detected in lizards from the epidemic area in the northwest of China. To date, few studies are focused on the natural infection of snakes with Leishmania . Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…infantum , further supporting previous studies in which Leishmania spp. pathogenic to mammals were molecularly detected in reptiles [ 44 46 ]. Accordingly, efforts should be made to isolate L .…”
Section: Discussionmentioning
confidence: 99%
“…infantum , further supporting previous studies in which Leishmania spp. pathogenic to mammals were molecularly detected in reptiles [ 44 46 ]. Accordingly, efforts should be made to isolate L .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the DNA and/or amastigote forms of pathogenic Leishmania spp. (i.e., Leishmania donovani , Leishmania tropica and Leishmania turanica ) have been detected in reptiles [ 22 25 ], therefore suggesting their potential role as reservoirs of mammalian pathogenic Leishmania spp. [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For leishmaniasis, the transmission occurs via the bite of infected female phlebotomine sand flies [7]. In addition, several publications demonstrated that a variety of animals can serve as potential reservoirs of both Trypanosoma [21][22][23] and Leishmania [24][25][26]. Therefore, the investigation of animal reservoirs would contribute to a better understanding of the biology of pathogens and the effective control of disease transmission.…”
Section: Discussionmentioning
confidence: 99%